Guanidino Compounds in the Elderly - Haruki, Katsuo; Koni, Ichiro; Hatakeyama, Syuichi; Takeda, Ryoyu; Matsumura, Masami; Hirata, Masayoshi; Tofuku, Yohei; Kuroda, Masahiro; Itoh, Masanori (Nihon Rōnen Igakkai zasshi, 1992)
To examine the metabolism of guanidino compounds in the elderly, we measured the serum concentrations of urea nitrogen, creatinine (Cr), guanidinoacetic acid (GAA) and creatine (CR) in middle-aged and elderly subjects. We also measured muscle mass in the elderly. The elderly subjects tended to have lower serum GAA concentrations than middle-aged subjects. On the contrary, CR concentrations of elderly subjects were higher than those of middle-aged subjects. Bedridden elderly subjects tended to have lower serum GAA concentrations and lighter muscle mass than ambulatory elderly subjects. On the contrary, serum CR concentrations of bedridden subjects were higher than those of ambulatory subjects. CR is an essential substance for muscle energy metabolism. These results indicate that high serum CR concentrations due to low CR metabolism in skeletal muscle might suppress glycine amidinotransferase (GAT) activity, resulting in decreased GAA production in the elderly.